2021
DOI: 10.3991/ijet.v16i11.23319
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Factors Affecting Student Participation in Peer-Assisted English Learning Based on Online Education Platform

Abstract: Through a questionnaire survey, this study explored the factors affecting student participation in peer-assisted English learning (PAEL) based on online education platforms. Specifically, the authors constructed the system of PAEL contents, analyzed the online PAEL behaviors of students, and evaluated the student participation in online PAEL from both surface participation and deep participation. On this basis, the influencing factors of student participation in online PAEL were evaluated thoroughly. In the en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Furthermore, the concept has shown its potential to be adopted into our existing educational learning structures. Recent studies on participation in classroom settings (see [24], [47]- [49]) found that participation through helping empowers learners to perform individual and group tasks, and that low motivation to participate affect learners' behavior.…”
Section: Helpers To Increase Participationmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the concept has shown its potential to be adopted into our existing educational learning structures. Recent studies on participation in classroom settings (see [24], [47]- [49]) found that participation through helping empowers learners to perform individual and group tasks, and that low motivation to participate affect learners' behavior.…”
Section: Helpers To Increase Participationmentioning
confidence: 99%
“…Hammond [21] found 'communicative learners' within early online forums, people who showed greater involvement and took on the role of supporting a group. Various researchers (see [22]- [24]) explored various motivations to participate online. They concluded that the reason to help emerges from a general satisfaction in sharing experiences/ knowledge with others and a belief that one can learn by explaining even if the explanations concern the problems of beginners.…”
mentioning
confidence: 99%
“…e rapid development of the new generation of information technology and its universal application in colleges and universities have promoted the profound changes of campus informatization [1]. At the same time, with the popularization of intelligent mobile terminals and the development of high-speed communication networks, mobile learning will become the main trend of learners' learning style in the future.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the traditional teaching platform is basically oriented to the learning mode of fixed places, lacking the services and functions oriented to mobile learning, which has certain defects. For example: (1) the degree of teaching resources is limited, and there is a lack of resource sharing mechanism for coconstruction and sharing. Most resources can only be opened to authorized users.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of non-academic support, foreign online learning platforms mainly provide learning consulting services, personalized daily management, online learning process monitoring services, technical failure services, emotional care services, etc. These services are very mature in foreign countries and have been recognized by many online learners [3].…”
Section: Introductionmentioning
confidence: 99%